Conscription and crime: evidence from the Argentine draft lottery - Sebastian Galiani; Martín A. Rossi; Ernesto Schargrodsky (Fondazione Eni Enrico Mattei (FEEM), 2010)
We estimate the causal effect of mandatory participation in the military service on the involvement in criminal activities. We exploit the random assignment of young men to military service in Argentina through a draft lottery to identify this causal effect. Using a unique set of administrative data that includes draft eligibility, participation in the military service, and criminal records, we find that participation in the military service increases the likelihood of developing a criminal record in adulthood. The effects are not only significant for the cohorts that performed military service during war times, but also for those that provided service at peace times. We also find that military service has detrimental effects on future performance in the labor market.
Keywords: K42; 330; Military Service; Violent behavior; Crime